Electromagnetics explained : a handbook for wireless/RF, EMC, and high-speed electronics - Schmitt, Ron. (Amsterdam ; Boston : Newnes, 2002)
"Written for engineers by an engineer, Electromagnetics Explained will teach you everything you need to know about RF/high-speed design and electromagnetic fields. Learn hands-on, practical solutions to EMI/EMC that you can apply immediately to your projects and products. Incorporating physical explanations and practical viewpoints substituted for mathematical theory, this book is accessible to technologists and technicians in addition to engineers, demystifying topics often considered "black magic." Through straightforward analogies and interesting examples ranging from lightning to electric guitars, the author provides an explanation of electromagnetic fields that is not only practical and informative, but also fascinating and exciting. Even readers with no background in electromagnetics will gain a deep and intuitive knowledge of the subject." "Based on familiar circuit theory and basic physics, this book serves as an invaluable reference for analog and digital engineers alike. For those who work with analog RF, this book is a must-have resource. With computers and networking equipment of the 21st century running at such high frequencies, it is now crucial for digital designers to understand electromagnetic fields, radiation, and transmission lines. This knowledge is necessary for maintaining signal integrity and achieving EMC compliance. Because many digital designers are lacking in analog design skills, let alone electromagnetics, an easy-to-read but informative book on electromagnetic topics will be a welcome addition to their professional libraries. Book jacket."--Jacket.
Introduction and survey of the electromagnetic spectrum -- Fundamentals of electric fields -- Fundamentals of magnetic fields -- Electrodynamics -- Radiation -- Relativity and quantum physics -- Hidden schematic -- Transmission lines -- Waveguides and shields -- Circuits as guides for waves and S-parameters -- Antennas: how to make circuits that radiate -- EMC -- Lenses, dishes, and antenna arrays -- Diffraction -- Frequency dependence of materials, thermal radiation, and noise.
Includes bibliographical references and index.
Keywords: Electronics; Radio; Electromagnetic theory; Radio broadcasting